Writing security tools and exploits - Foster, James C.; Liu, Vincent (Rockland, MA : Syngress, 2006)
Writing Security Tools and Exploits will be the foremost authority on vulnerability and security code and will serve as the premier educational reference for security professionals and software developers. The book will have over 600 pages of dedicated exploit, vulnerability, and tool code with corresponding instruction. Unlike other security and programming books that dedicate hundreds of pages to architecture and theory based flaws and exploits, this book will dive right into deep code analysis. Previously undisclosed security research in combination with superior programming techniques will be included in both the Local and Remote Code sections of the book. The book will be accompanied with a companion Web site containing both commented and uncommented versions of the source code examples presented throughout the book. In addition to the book source code, the CD will also contain a copy of the author-developed Hacker Code Library v1.0. The Hacker Code Library will include multiple attack classes and functions that can be utilized to quickly create security programs and scripts. These classes and functions will simplify exploit and vulnerability tool development to an extent never before possible with publicly available software. * Provides readers with working code to develop and modify the most common security tools including Nmap and Nessus * Learn to reverse engineer and write exploits for various operating systems, databases, and applications * Automate reporting and analysis of security log files.
Writing exploits and security tools -- Assembly and shellcode -- Exploits : stack -- Exploits : heap -- Exploits : format strings -- Writing exploits 1 -- Writing exploits 2 -- Coding for Ethereal -- Coding for Nessus -- Extending Metasploit 1 -- Extending Metasploit 2 -- Extending Metasploit 3.
Includes index.
Keywords: Computer security -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc